Lipids and lipid domains of the yeast vacuole. (19th October 2018) - Tsuji, Takuma; Fujimoto, Toyoshi
Abstract : The membrane raft has been a focus of intensive research for the past two decades. Liquid-ordered domains form in artificial liposomes containing sterol and saturated lipids, but their presence in living cell membranes has been controversial. The yeast vacuole is exceptional in that micron-sized raft-like domains form in the stationary phase and under several other conditions. The sterol content of the vacuole in the log phase is much lower than that of liposomes showing liquid-ordered domains, suggesting that sterols may need to be supplied to the vacuole for the raft-like domain formation. We will discuss how lipids and lipid domains are organized in the vacuolar membrane and examine whether evidence is strong enough to conclude that the observed micron-sized domains are rafts.